Characterization of the Microflow Through 3D Synthetic Niche Microenvironments Hosted in a Millifluidic Bioreactor - Ene-Iordache, Bogdan; Campiglio, Chiara Emma; Raimondi, Manuela Teresa; Remuzzi, Andrea (Frontiers in Bioengineering and Biotechnology, 2021)
Background Development of new medicines is a long-time process which is at risk of failure since drug efficacy measured in vitro is difficult to confirm in vivo. Intended to add a new device in drug discovery, the MOAB-NICHOID device was developed: the device is a miniaturized optically accessible bioreactor (MOAB) having the 3D cell-seeded scaffold NICHOID engineered inside. The aim of our study was to characterize the microflow through the 3D nichoid microenvironment hosted in the MOAB-NICHOID device. Methods We used computational fluid dynamics (CFD) simulations to compute the flow field inside a very fine grid resembling the scaffold microenvironment. Results The microflow inside the multi-array of nichoid blocks is fed and locally influenced by the mainstream flow developed in the perfusion chamber of the device. Here we have revealed a low velocity, complex flow field with secondary, backward, or local recirculation micro-flows induced by the intricate architecture of the nichoid scaffold. Conclusions Knowledge of the microenvironment inside the 3D nichoids allows planning of cell experiments, to regulate the transport of cells towards the scaffold substrate during seeding or the spatial delivery of nutrients and oxygen which affects cell growth and viability.